Township Violence, Levels of Distress, And Post-Traumatic Stress Disorder, Among Displacees from Natal - Michelson, Catherine L (PINS-Psychology in Society, 2026)
This paper focuses on research carried out in 1990 with victims of the Natal violence. Natal is one of the areas severely affected by violence. This is characterised by brutal attacks, injuries, deaths of thousands of people, loss and destruction of property, and the uprooting, fragmentation and dislocation of communities. The study examined the relationship between exposure to violent incidents, levels of distress, and post-traumatic stress disorder (PTSD) among displacees of the 1990 violence in Natal. The first hypothesis was that exposure to traumatic events at the time of the conflict would have direct effects on levels of distress. Secondly, because displacees were exposed to a range of violent events outside normal human experience, it was hypothesized that many would display symptoms of PTSD. The sample consisted of 120 displacees who had fled their homes following violent attacks on their community, and were staying in refugee camps in the Pietermaritzburg area. The incidence of PTSD and levels of distress were measured by the Post-Traumatic Stress Disorder Inventory adapted for displacees. A brief interview schedule to obtain demographic information and details pertaining to traumatic experiences during the conflict was devised for this study. Results indicated an 87% incidence of PTSD within the sample, indicating that the majority of the sample were expressing symptoms of distress associated with the trauma they had experienced. More specifically, factors such as witnessing killings, the death of family members or friends, or being injured at the time of the conflict, were found to significantly affect the levels of distress reported. Implications of these findings are discussed.